Food preservation by cold plasma from dielectric barrier discharges in agri-food industries - Jiang, Hao; Lin, Qian; Shi, Wenqing; Yu, Xiuzhu; Wang, Shaojin (Frontiers in Nutrition, 2022)
Background: Cold plasma (CP) can be defined as partially or wholly ionized gas carrying myriads of highly reactive products, like electrons, negative ions, positive ions, free radicals, excited or non-excited atoms, and photons at ambient temperature. It is generated at 30–60°C under atmospheric or reduced pressure (vacuum). It requires less power, exhibits electron temperatures much higher than the corresponding gas (macroscopic temperature), and does not present a local thermodynamic equilibrium. The dielectric barrier discharges (DBD) are one of convenient and efficient methods to produce CP. Scope and Approach: CP technology holds potential to replace conventional decontamination methods for agri-food processing, through the reduced bacterial levels at harvest, the pest and mycotoxin removal, decontaminants, and catalysis/modification, due to its low energy requirement and flexibility in system design. It can meet microbial food safety standards, improve the physical, nutritional and sensory characteristics of the products, preserve unstable bioactive compounds, and modulate enzyme activities. This manuscript also discusses the quality characteristics of food components before/after CP treatment. Key Findings and Conclusions: In the past decade, CP treatments of food products have experienced increased popularity due to their potential contributions to non-thermal food processing. There is no doubt that CP treatment is a flexible approach with demonstrated efficacy for controlling many risks across food and agriculture sustainability sectors. In addition, CP technologies also can be applied on the food related area, including modification of chemical structures and desensitization treatments. There is a need to fully assess the benefits and risks of standalone CP unit processes or their integration as a processing chain as soon as the economic, ecological and consumer benefits and acceptability are considered.